Is Inequality Bad for Business : A Nonlinear Microeconomic Model of Wealth Effects on Self-Employment - Mesnard, Alice; Ravallion, Martin (World Bank, Washington, DC, 2014)
It is widely assumed that pervasive credit market failures mean that a person's current wealth is critical to whether or not that person can take up opportunities to start a new business. The authors show that inequality in wealth can be either good or bad for the level of entrepreneurship in an economy, depending on how diminishing returns to capital interact with borrowing constraints at the microeconomic level. They use nonparametric regression methods to study wealth effects on business start-ups among migrants returning to their home country, Tunisia. They include controls for heterogeneity, with specification tests for the nonseparable effects with wealth and for selection bias. There is no evidence of increasing returns at low wealth. The aggregate number of business start-ups is an increasing function of aggregate wealth but a decreasing function of wealth inequality. In other words, at any given mean, the higher the initial inequality of wealth, the lower the rate of new business start-ups, through the existence of diminshing returns to capital given liquidity constraints. In this sense, the results suggest that inequality is bad for business--but the size of this effect is small. The findings do not constitute a case for public redistribution of wealth as a means of stimulating business activity. There should probably be more research on interventions to reduce liquidity constraints.